The Role of Muslim Women in Waste Management for Sustainable Environmental Conservation in the Coastal Area of Bone, South Sulawesi - Nur, Suriani; Utami, Sari; Duraesa, M. Abzar; Yahya, M.; Sohyb, Muh. Nizar (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
The global world is facing environmental and coastal ecosystem degradation, including Indonesia, a region largely comprised of marine and coastal areas that relies heavily on marine ecosystems. This study aims to examine the role of Muslim women in household waste management in coastal areas, framed by Islamic principles of environmental management. Using a mixed method approach, incorporating both Islamic and environmental approaches, data were collected through surveys, interviews, documentation and observation. Interviewees included academics, religious scholars, environmental agencies, the Office of Religious Affairs, and coastal communities. The documents analyzed included legal regulations, articles, and books related to the content of the articles. The study found that Muslim women, as primary educators in their households, play a crucial role in fostering environmental awareness and promoting sustainable waste management practices. Involvement in religious study groups enhances their knowledge and attitudes toward environmental preservation. Islamic teachings emphasizing cleanliness and the obligation to protect the environment serve as fundamental motivations for adopting and promoting environmentally responsible behavior. These collective efforts contribute to the preservation of coastal ecosystems and the advancement of sustainable development goals. Furthermore, effective waste management aligns with Islamic values, positioning it as both a practical environmental initiative and a form of worship.